Methodology Of Teaching Students To Describe Still Life Composition - Ulfat Shuhratovich Ismatov (Academia One Publishing, 2023)
This article is intended for all pedagogical artists working in the field of visual arts. The article briefly discusses the rules of still life composition.
Keywords: Composition; Still life; fine art; artist